Draft Eighth Five Year Plan 1990-95 Annual Plan 1991-92 Government of Punjab - Planning Commission (Planning Commission, 1990)
The Seventh Plan size of the Punjab State had been fixed at Rs. 3,285.00 crores against which an expenditure of Rs. 3,547.27 crores was incurred, performance being, 107.98%. An outlay of Rs. 905.00 crores has been approved for the Annual Plan . 1990-91. Keeping in view the guidelines of the Planning Commission and unstable conditions prevailing in the State outlay for the Eighth Five Year Plan 1990—95 is proposed at Rs. 6,663.42 crores. the allocation of Rs. 1,280.12 crores has been proposed for the Annual Plan 1991-92.
Department of Planning Government of Punjab